Pelaksanaan Informed Consent Dan Informed Choice Antara Dokter Spesialis Kandungan Dengan Akseptor KB Pada Tindakan Medis Sterilisasi Di Puskesmas Kecamatan Wonosari Kabupaten Klaten - Vivi Kurniawati (FH UMY, 2014)
The purpose of this research to find an obstetrician civil liability as a result of bleeding in the sterilization of medical action. Of medical measures that resulted in the loss indicates a lack of caution in dealing with the content spesilis physician medical treatment to the acceptors KB of sterilization which led to acceptable losses. This research is a kind of normative law and empiric law research by using qualitative approach. This research was conducted at the District Health Center Wonosari Klaten district. The technique of collecting data use technique of interview and document study or literature study in this case the literature material used books and the rule of laws. The technique of data analysis used the analysis technique of qualitative data by using interactive method. The conclusion of this study is physician civilly liable for negligence or lack of awareness when sterilization of medical action to the acceptors KB. The author recommends that physicians provide information to the patient in terms of the implementation of any medical treatment, must be provided with a transparent and clearly, and then appealed to the government to fund for compensation in medical services should be maximized. Keywords: implementation of informed consent and informed choice, accountability obstetrician and acceptors KB.